Fotoatividade de óxidos mistos Nb2O5/TiO2 aplicados na degradação do herbicida ácido 2,4-diclorofenoxiacético - Fávaro, Yuri Barros (2022)
In the present work, syntheses of niobium, titanium and mixed oxides (Nb2O5/TiO2) were carried out by two chemical mixture methodologies: modified solgel and modified Pechini. The photocatalysts were characterized by techniques such as: thermogravimetric analysis (TGA), Xray diffraction (XRD), scanning electron microscopy (SEM), energy diffusive spectroscopy (EDS) and zero charge point (PCZ). The semiconductors were applied for the degradation of the herbicide 2,4dichlorophenoxyacetic acid, by photocatalytic process, guided by the experimental design of central compound varying the parameters: pH, calcination temperature and catalyst concentration. Results such as those presented by photolysis with 88% degradation of the pollutant, Nb2O5 and TiO2 as values above 98% removal, as well as mixed oxides in molar ratios (Nb2O5: TiO2 = 25:75, 50:50 and 75:25), under reaction conditions of pH 3.0 and catalyst concentration 0.5 g L1, proved to be significant for the removal of 2,4D.